Agent-based modelling for early-stage optimization of spatial structures. (March 2023) - Zargar, Seyed Hossein; Sadeghi, Jaleh; Brown, Nathan C.
Agent-based modelling (ABM) is a complex problem-solving approach that can be employed in early-stage parametric design, and certain design applications may benefit from such a bottom-up strategy. This research investigates the potential of ABM for structural design optimization. A case study of a form-found cantilevered truss is presented that has a doubly curved shape over a regular grid, resulting in individual members with different lengths across the structure. It is hypothesized that an agent-based approach might generate an irregular grid of similar or better structural performance, but with more uniform length of individual elements. This approach could be useful when designing a global structural form from a kit of parts or adaptively reusing a disassembled existing structure with regular member lengths. A series of ABM simulations are conducted with different hyperparameters, and the generated designs are compared to the original form-found shape in terms of structural performance.